Burgas Planning a Black Sea smart city (Volume 5) - Field, Brian (European Investment Bank, 2019)
Burgas regularly tops the list of best places to live in Bulgaria. Whether enjoying a walk through the resplendent Sea Garden, relaxing on the beautiful central city beach, or enjoying a drink and fresh grilled fish at one of the many outdoor bars and restaurants, it is easy to see why tourists like it so much. A key challenge for the city, however, is to extend this good feeling to the off-season, when tourists are few, the economy is less animated, and the central area is almost comatose after dark. The city aims to deliver this transformation with its smart city agenda.